Safety of monitoring antiretroviral therapy response in HIV-1 infection using CD4+ T cell count at long-term intervals - Ingridt Hildegard Vogler; Daniela Frizon Alfieri; Heloisa Damazio Bruna Gianjacomo; Elaine Regina Delicato de Almeida; Edna Maria Vissoci Reiche (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Abstract: The latest Brazilian guideline recommended the reduction of routine CD4+ T cell counts for the monitoring of patients with human immunodeficiency virus type 1 (HIV-1) under combination antiretroviral therapy (cART). The aim of this study was to evaluate the safety of monitoring response to cART in HIV-1 infection using routine viral load at shorter intervals and CD4+ T cell count at longer intervals. CD4+ T cell counts and HIV-1 viral load were evaluated in 1,906 HIV-1-infected patients under cART during a three-year follow-up. Patients were stratified as sustained, non-sustained and non-responders. The proportion of patients who showed a CD4+ T > 350cells/µL at study entry among those with sustained, non-sustained and non-responders to cART and who remained with values above this threshold during follow-up was 94.1%, 81.8% and 71.9%, respectively. HIV-1-infected patients who are sustained virologic responders and have initial CD4+ T cell counts > 350cells/µL showed a higher chance of maintaining the counts of these cells above this threshold during follow-up than those presenting CD4+ T ≤ 350cells/µL (OR = 39.9; 95%CI: 26.5-60.2; p < 0.001). This study showed that HIV-1-infected patients who had sustained virologic response and initial CD4+ T > 350cells/µL were more likely to maintain CD4+ T cell counts above this threshold during the next three-year follow-up. This result underscores that the evaluation of CD4+ T cell counts in longer intervals does not impair the safety of monitoring cART response when routine viral load assessment is performed in HIV-1-infected patients with sustained virologic response.